Daptomycin Associated Rhabdomyolysis with Concurrent Use of Atorvastatin (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Hospital Medicine; Case Report